The unbreakables : a novel - Barr, Lisa (Harper, 2019)
The worst birthday ever might just be the gift of a lifetime<U+2026> It<U+2019>s Sophie Bloom<U+2019>s forty-second birthday, and she<U+2019>s ready for a night of celebration with Gabe, her longtime, devoted husband, and her two besties and their spouses. Dinner is served with a side of delicious gossip, including which North Grove residents were caught with their pants down on Ashley Madison after the secret on-line dating site for married and committed couples was hacked. Thirty-two million cheaters worldwide have been exposed<U+2026>including Sophie<U+2019>s “perfect” husband. To add insult to injury, she learns Gabe is the top cheater in their town. Humiliated and directionless, Sophie jumps into the unknown and flees to France to meet up with her teenage daughter who is studying abroad and nursing her own heartbreak. After a brief visit to Paris, Sophie heads out to the artist enclave of Saint-Paul-de-Vence. There, for the first time in a long time, Sophie acknowledges her own desires<U+2014>not her husband<U+2019>s, not her daughter<U+2019>s<U+2014>and rediscovers her essence with painful honesty and humor, reawakening both her sensuality and ambitions as a sculptor.